DEVELOPMENT OF INTERACTIVE LEARNING MEDIA TO IMPROVE LEARNING LOCAL SCRIPT IN SUMBAWA - Gina Anggraini; Asrin Asrin (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
The local script is one of the nation's cultural treasures. One of the local characters owned by the Indonesian people is the Satera Jontal script. Satera Jontal is a local script from Sumbawa, West Nusa Tenggara. This script is used to write and read the Sumbawa language which was spoken on the western part of the island of Sumbawa in the past. The purpose of this research is to increase student interest in learning Sumbawa script through interactive learning media. Research Methods This research uses a quantitative descriptive approach. Retrieval of data in this study was collected through a survey method by distributing questionnaires to elementary school (SD) children in grade VI (six). The survey was conducted to determine the interest in learning Sumbawa (Sumatran Jontal) characters through the use of interactive learning media. The results showed that students' interest in Sumbawa script was still very low. Therefore, efforts are made to increase student interest in learning Sumbawa script. These efforts must pay attention to the following: the interactive learning media used must be appropriate so that it makes it easier for students to learn Sumbawa script.